RELASI KUASA PEMERINTAH DESA DAN PETANI DALAM PEMBANGUNAN PERTANIAN: STUDI DI DESA NGLANGGERAN, KECAMATAN PATUK, KABUPATEN GUNUNGKIDUL - Dasifa, Yohanis (Penerbit Lafadz Jaya, 2026)
Agricultural development at the village level cannot be separated from power relations between the village government and farmers as key actors. These relations are reflected not only in formal policies but also operate through everyday practices involving decision-making processes, resource distribution, and the implementation of development programs. This article aims to analyze how power relations between the village government and farmers are formed, exercised, and negotiated within the practice of collaborative governance in agricultural development in Nglanggeran Village, Patuk District, Gunungkidul Regency. This study employs a qualitative approach with a case study design. Data were collected through in-depth interviews with village government officials, leaders and members of farmer groups, as well as other relevant actors, complemented by field observations and document analysis. Data analysis was conducted using a descriptive-interpretative method to capture the dynamics of actor interactions, decision-making mechanisms, and collaborative practices in village-level agricultural development. The findings indicate that power relations between the village government and farmers are dynamic and not entirely hierarchical. The village government exercises structural power through formal authority in planning and budgeting, while farmers possess productive power derived from local knowledge and practical farming experience. These relations shape collaborative patterns characterized by negotiation, normalization, and mutual dependence. This article concludes that sustainable agricultural development requires a more reflective and participatory management of power relations, so that farmer empowerment does not remain merely at the discursive level.